The Dialectic of Humanism in Islamic Education by Muhammadiyah and Nahdlatul Ulama as an Evolution of Social and Religious Thought in Indonesia - Rochmatul Muna; Kuntum Khairan Nisa; M. Husnaini (Universitas Islam Negeri Sumatera Utara, 2026)
This study discusses the dialectics of Islamic humanism within the educational traditions of Muhammadiyah and Nahdlatul Ulama (NU) as a form of the evolution of socio-religious thought in Indonesia. The purpose of this research is to analyze how humanitarian and Islamic values are integrated into the educational systems of these two organizations. The study employs a qualitative approach with a library research method through the analysis of relevant scholarly literature. The results indicate that Muhammadiyah highlights a rational and modern form of humanism through an integrative education that combines religious and general sciences. Meanwhile, NU emphasizes a spiritually and culturally based humanism through the pesantren system, which instills the values of compassion, tolerance, and moderation. Although differing in methods and orientations, both organizations share a common goal: to develop individuals who are faithful, knowledgeable, and morally upright. The dialectics between tradition and modernity shape an Islamic education model that is humanistic, adaptive, and contextual to contemporary developments. Thus, Islamic humanism within Muhammadiyah and NU education plays a crucial role in realizing a moderate, inclusive, and civilized form of Islam amid the challenges of globalization.